RESEARCH ON ACTIVE CONTROL OF VARIABLE MASS SEAT SUSPENSION USING PD CONTROL - AN CunSheng; CHEN XiaoLiang; WEI WeiZhen; LIU Kui (Jixie qiangdu)
Aiming at the system non-linearity caused by the change of load mass of seat suspension and the effective control of seat vibration, an active control system of variable mass seat suspension based on the proportional-derivative (PD) control was proposed. The proposed control system structure was based on several different controllers. The primary controller was used to evaluate the actual value of the main force that should be generated in the suspension system, and the secondary controller was used to calculate the instantaneous value of the signal that controled the active element through its reverse model. The active seat suspension system model was established, and the active seat suspension control system was designed. The robustness of seat suspension system with different load mass was verified by simulation. The controller parameters were optimized to realize the fine control of adaptive quality identification of active seat suspension. The optimized design results were compared and verifed, and the results show that the influence of mass change on the dynamic performance of active seat suspension system is significantly reduced. Under 100 kg mass load and EM3、 EM5 and EM6 excitation signals, the SEAT factor of the active system is reduced respectively by 49.81%, 20.96% and 29.85%. At the same time, the suspension stroke is reduced respectively by 4.76%, 33.87% and 18.18%. The active control system established in this paper significantly improves the performance of the seat suspension, and has better robustness to the varying load mass, which provides a reference for the research on the vibration isolation performance of the active seat suspension.